The Tabulae Eclypsium by Giovanni Bianchini - Chabás, José; Goldstein, Bernard R. (Aestimatio)

(untitled) (Institute for Research in Classical Philosophy and Science, 2021)
The Tabulae eclypsium by Giovanni Bianchini (d. after 1469) was part of a larger work, the Flores Almagesti, on mathematical astronomy. In his work on eclipses, which hitherto has not been studied in depth, Bianchini compiled new tables, strictly adhering to Ptolemy’s procedures, and explained their use by means of worked examples to facilitate the task of computers. Bianchini’s works were influential among his contemporaries, especially Peurbach and his student Regiomontanus, with whom Bianchini corresponded. For a variety of reasons, Regiomontanus’ works have eclipsed Bianchini’s. In this article, we present one of Bianchini’s major works, with the aim of restoring a more balanced perspective on 15th-century mathematical astronomy in Europe.